2023
DOI: 10.1177/08839115221149726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of triacetin on mechanical strength and free surface energy of PHBHHx: The prevention of intra-abdominal adhesion

Abstract: Several polymers are used for the preparation of biomaterials as membranes and films for tissue engineering applications. The most common plasticizer is PEG to obtain polymer-based biomaterials. On the other hand, triacetin is a non-toxic, FDA-approved plasticizer mostly used in the food industry. In this study, we used triacetin as a plasticizer to obtain hydrophobic membranes for the prevention of intra-abdominal adhesion. We selected a well-known polymer named PHBHHx which is a bacterial polyester generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Studies have shown that coating, seeding, or embedding various therapeutic agents makes the biomaterial more effective for the targeted treatment. 39,40 Common features of these biomaterials are being biodegradable, biocompatible, bioresorbable, having non-toxic metabolic compounds, and providing controlled release. Controllable release from the biomaterial maintains an optional dose of the contents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that coating, seeding, or embedding various therapeutic agents makes the biomaterial more effective for the targeted treatment. 39,40 Common features of these biomaterials are being biodegradable, biocompatible, bioresorbable, having non-toxic metabolic compounds, and providing controlled release. Controllable release from the biomaterial maintains an optional dose of the contents.…”
Section: Discussionmentioning
confidence: 99%